The structure and sickness rate of eye and adnexa diseases in children in Ukraine. - Vіtovska O. P.; Savіna O. M. (Medicni Perspektivi, 2015)
The purpose of the work is to estimate sickness rate and patterns of eye and adnexa diseases. The data of departmental statistical reports of Ministry of Health of Ukraine (form 12) for 2005-2014 years, period were used. The specific weight, prevalence and sickness rate were determined for the following diseases: conjunctivitis and other diseases of the conjunctiva, cataract, myopia - among children aged 0-17 years; strabismus - among children aged 0-14 years; glaucoma and optic nerve atrophy - among adolescents aged 15-17 years.Results. Among children’s eye and adnexa diseases the following diseases wereidentified the most often: myopia (28,26 ± 0,02)%, conjunctivitis (20,12±0,01)% and strabismus (7,87±0,01)%; particularly among new cases of eye diseases their proportions were 13,89±0,02%, 44,06±0,03% and 2,24±0,01% correspondingly. The prevalence of eye and adnexa diseases among children in Ukraine was 102,05±0,03%, and 45,90±0,02% especially for newly diagnosed diseases.